Assessing Critical Thinking Skills in Academic Writing: A Study of English Education Students at University of Mataram - Nita Pujiana; Untung Waluyo; Henny Soepriyanti (Jurnal Ilmiah Profesi Pendidikan, 2025)
In higher education, critical thinking plays a vital role in shaping students’ analytical and reflective abilities, particularly through academic writing which serves as both a learning tool and an assessment method. Recognizing its importance, this study investigated the critical thinking skills of English Department students at the Faculty of Teacher Training and Education, University of Mataram, as reflected in their academic writing. The study aimed to assess the level of students’ critical thinking skills, identify their strengths and weaknesses, and explore the factors that influence their critical thinking development. Employing a sequential explanatory mixed-method design, quantitative data were first collected through IELTS aligned academic writing tasks from 45 fourth semester students, followed by qualitative interviews to gain deeper insights into their reasoning processes and writing challenges. Quantitative findings indicated that students reached a general intermediate level of critical thinking, in which they exhibited relative strength in task response and coherence but consistent weakness in grammar and vocabulary use. Comparative outcomes indicated that Class G outperformed consistently Class H on key performance indicators. Qualitative findings also revealed that while students were able to use evidence and reason, they lacked analytical depth, integration of sources, and structural composition in argument construction. Lecturers' feedback, peer interaction, and self-regulation were identified as key factors supporting students' critical thinking development. The study concludes that academic writing can serve as an effective medium for developing students’ critical thinking skills when supported by explicit instruction, rubric-based feedback, and collaborative learning activities. It highlights the need for continuous pedagogical innovation to strengthen students’ ability to think critically and express their ideas effectively in academic contexts.